Pengaruh Kehalusan Bahan Terhadap Karakteristik Fisik dan Kimia Kitosan dari Limbah Maggot Black Soldier Fly (Hermetia illucens): Effect of Material Fineness on the Physical and Chemical Characteristics on Chitosan from Black Soldier Fly (Hermetia illucens) Waste - Rahma, Imas Nabila; Budiati, Titik (JOFE : Journal of Food Engineering, 2024)
Maggot is the larva of the Black Soldier Fly (Hermetia illucens) which has a fairly high animal protein content and has the potential to be the main ingredient for chitosan because it contains chitin. The aim of this research is to determine the effect of material fineness on the physical and chemical characteristics of chitosan obtained from black soldier fly (Hermetia illucens) waste. Making chitosan from black soldier fly (Hermetia illucens) waste using samples of whole maggot casings and crushed maggot casings (60 mesh) is carried out through the stages of deproteination, demineralization, depigmentation and deacetylation. The test results show that the fineness of the material can influence the ash content, chitosan yield, and degree of deacetylation. The fineness of the material does not affect the water content. The sample with the best treatment, namely the maggot casing sample, was ground to a size of 60 mesh. The characteristics of BSF chitosan give a pH of 7, water content of 5.48% and 4.38%, ash content of 0.36% and 4.39%, yield content of 23.67% and 13.94%, and degree of deacetylation of 82 and 63,09.